An over time comparison of linear and spatial regression model parameters to predict average housing values: Evidence from two Canadian cities - Maoh, Hanna; Abdo, Mohamed (The Canadian geographer, 2025)
Residential real estate models are a key component of planning support systems, which aid in shaping future urban land use and transportation. These models typically rely on parameters estimated from historical data corresponding to a specific base year, assuming that such parameters remain stable over time. This paper examines the temporal stability of parameters linked to variables influencing average housing values at the dissemination‐area level. It does so by comparing parameter estimates across multiple time periods in two Canadian cities: Ottawa, Ontario and Calgary, Alberta. Using Canadian census data, pooled regression analyses were conducted for the years 2006, 2011, and 2016 to model average housing values. The findings indicate general consistency in the factors affecting housing values across both cities. Interestingly, the parameters of the Ottawa pooled models suggest strong stability over time compared to Calgary. Additionally, the Spatial Autoregressive model outperformed both linear and spatial error models in terms of accuracy and predictive performance . Les modèles de développements résidentiels constitue un élément clé des systèmes de soutien à l’urbanisme car ils aident à façonner l’utilisation du sol et les transports en milieu urbain. Ces modèles s’appuient généralement sur des paramètres estimés à partir de données historiques correspondant à une année de référence spécifique. Ces paramètres sont présumés stables. Cet article analyse la stabilité temporelle des paramètres liés aux variables influençant la valeur moyenne des logements à l’échelon des aires de diffusion de Statistique Canada. Plus précisément, nous comparons les estimations des paramètres sur plusieurs périodes dans deux villes canadiennes, soit Ottawa, en Ontario, et Calgary, en Alberta. À partir des données du recensement canadien, des analyses de régression groupées ont été effectuées pour les années 2006, 2011 et 2016 afin de modéliser la valeur moyenne des logements. Les résultats indiquent une cohérence générale des facteurs influant sur la valeur des logements dans les deux villes. Fait à noter, les paramètres des modèles groupés d’Ottawa suggèrent une forte stabilité dans le temps comparés à ceux de Calgary. De plus, le modèle d’auto‐régression spatiale a surpassé les modèles d’erreur linéaires et spatiaux en termes de précision et de capacité prédictive . Average housing values at the dissemination‐area level are examined across three census years in two Canadian metropolitan regions. The modeling results demonstrate that the selected explanatory variables remain consistent over time, especially for Ottawa. Spatial lag models outperform traditional linear and spatial error regression models in both explanatory power and predictive accuracy.